PENGARUH RETURN ON ASSETS, RETURN ON EQUITY, NET PROFIT MARGIM, ECONOMIC VALUE ADDED, DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM (Studi pada Perusahaan Food and Beverage yang tercatat di Bursa Efek Indonesia Periode 2013-2015) - Rotua Margaret Oktavia Hutabarat (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This thesis aims identifying the effect of Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Economic Value Added (EVA), and Market Value Added (MVA) on the stock return of food and beverage companies listed in the Indonesia Stock Exchange in the period of 2013-2015. This thesis takes all food and beverage companies listed in the Indonesia Stock Exchange as its population. Using purposive sampling, 10 food and beverage companies were selected. The analysis technique used in this research is multiple linear regression analysis. The results shows that MVA has significant effect on stock return. While ROA, ROE, NPM, and EVA have no significant effect on stock return.Keywords: Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Economic Value Added (EVA), Market Value Added (MVA) and Stock Return.